Moderating Role Of Shariah Committee Quality On The Relationship Between Audit Committee And Malaysian Takaful Performance : A Literature Review - MontherEldaia; Mustafa Mohd Hanefah; Ainulashikin Marzuki; Saddam Ali Shatnawi (Postgraduate of IAIN Metro Lampung, Indonesia, 2024)
Non-Indexed Publication